A comparison of in vitro fertilization potential of sperm obtained from refrigerated (4°C) epididymis and fresh ejaculation of buck under different embryo culture media - KUMAR, DHARMENDRA; JAIN, SALIL KUMAR; SARKHEL, BIKASH CHANDRA (The Indian Journal of Animal Sciences, 2016)
The present study assessed the fertilization potential of sperm obtained from refrigerated epididymis and fresh ejaculation of buck under 2 culture media, viz. modified synthetic oviductal fluid (mSOF) and research vitro cleave-blastocyst (RVCL-BLAST) media. In the process, the cauda epididymis of slaughtered buck were immediately collected, pre-processed and refrigerated (4°C) for 24 h. The oocytes recovered from slaughter house ovaries were in vitro matured and fertilized with both semen sources. On analysis of embryonic development, ejaculated group showed significantly higher blastocyst rate than epididymal sperm, however, initial cleavage rates of epididymal group was significantly higher than ejaculated semen, irrespective of culture media. Among the culture media, RVCL-BLAST media was significantly efficient than mSOF in terms of cleavage and blastocysts, irrespective of gametes sources. Despite of lower outcome of blastocyst, cold stored epididymal sperm may be considered as an alternative, potent and viable source of gametes for assisted reproduction in case of endangered or other livestock, if immediate facilities for sperm processing are not available.